2018
DOI: 10.1002/cam4.1834
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant CpG‐methylation affects genes expression predicting survival in lung adenocarcinoma

Abstract: Lung adenocarcinoma (LUAD) is a common diagnosed disease with high‐mortality rate, and its prognostic implications are under discovered. DNA methylation aberrations are not only an important event for dysregulation of gene expression during tumorigenesis but also a revolution in epigenetics by identifying key prognostic biomarkers for multiple cancers. In this study, we analyzed methylation status of 485 578 CpG sites and RNA‐seq transcriptomes of 20 532 genes for 1095 LUAD samples in TCGA database. The associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 41 publications
(63 reference statements)
0
19
0
Order By: Relevance
“…de Almeida and other colleagues [ 14 ] analyzed the DNA methylation and gene expression data between breast cancer tissue and corresponding normal tissue in TCGA and found that cg12374721 (PRAC2), cg18081940 (TDRD10), and cg04475027 (TMEM132C) could be used as diagnostic and prognostic markers in breast cancer. He and other experts [ 21 ] analyzed the methylation status of CpG sites and the RNA-seq data of LUAD in TCGA database to explore the relationship regarding the prognostic value between DNA methylation and corresponding gene expression, and then 10 genes were found to be related to the prognosis of patients, indicating that they may be therapeutic targets of LUAD. Although there have been studies on biomarkers for prognosis of LUAD, most of the biomarkers cannot help to accurately predict the prognosis of patients with LUAD.…”
Section: Introductionmentioning
confidence: 99%
“…de Almeida and other colleagues [ 14 ] analyzed the DNA methylation and gene expression data between breast cancer tissue and corresponding normal tissue in TCGA and found that cg12374721 (PRAC2), cg18081940 (TDRD10), and cg04475027 (TMEM132C) could be used as diagnostic and prognostic markers in breast cancer. He and other experts [ 21 ] analyzed the methylation status of CpG sites and the RNA-seq data of LUAD in TCGA database to explore the relationship regarding the prognostic value between DNA methylation and corresponding gene expression, and then 10 genes were found to be related to the prognosis of patients, indicating that they may be therapeutic targets of LUAD. Although there have been studies on biomarkers for prognosis of LUAD, most of the biomarkers cannot help to accurately predict the prognosis of patients with LUAD.…”
Section: Introductionmentioning
confidence: 99%
“…The past decade has witnessed rapid progress in next-generation sequencing and its increasing application in preclinical practice. In recent years, several studies have attempted to associate the transcriptome or epigenome with the clinical outcomes of patients with LUAD (Selamat et al, 2012; Zhang et al, 2017; Gao et al, 2018; He et al, 2018). Zhang et al analyzed and validated the expression profiles and prognostic values of the mRNAs of five differentially expressed genes associated with DNA methylation in LUAD (Zhang et al, 2017), increasing the likelihood that altered signature genes will become useful biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al analyzed and validated the expression profiles and prognostic values of the mRNAs of five differentially expressed genes associated with DNA methylation in LUAD (Zhang et al, 2017), increasing the likelihood that altered signature genes will become useful biomarkers. Using a TCGA dataset, He et al (2018) disentangled the relationships between aberrant CpG-methylation and gene expression to identify 10 aberrantly methylated and dysregulated genes. However, their study only focused on the ability of individual genes to predict OS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…is remaining a promising field since there is no widely accepted approach for it. The most common processes to compare different omics data are by (i) comparing the gene lists produced at the end of each individual analysis, with the assumption that overlapping genes were influenced by different mechanisms (6,7) and (ii) checking the correlation of two events that are associated with the same gene, using statistical methods such as spearman or pearson correlation test (8,9). However, as interactions in biological systems are generally not linear, methods such as PCA, Bayesian or non-Bayesian networkbased were applied as extended data integration approaches (10).…”
Section: Introductionmentioning
confidence: 99%